Effects of dietary nitrate and caffeine on end power and work above end power during a 3 min all-out test in trained male cyclists - Hagele, A. M.; Sunderland, K. L.; Mumford, P. W.; Kerksick, C. M. (Nutrients, 2026)
Background: The purpose of this study was to examine the effects of acute dietary nitrate (NO3-) and caffeine (CAF) supplementation on end power (EP) and work performed above EP (WEP) in trained male cyclists during a 3 min all-out test (3MT) on a cycle ergometer. Methods: Fifteen healthy, trained male cyclists (28.5 ± 5.3 years, 79.2 ± 9.1 kg, VO2peak 55.2 ± 5.6 mL·kg-1·min-1) completed four exercise trials in a randomized, double-blind, placebo-controlled, crossover study design separated by 3-7 days. The four experimental conditions were placebo beverage (nitrate-depleted) + placebo capsule, nitrate-rich beetroot juice + placebo capsule (BR), placebo beverage + caffeine capsule (CAF), and nitrate-rich beetroot juice + caffeine capsule (BR + CAF). Participants consumed nitrate-rich beetroot juice (~13 mmol NO3-) or nitrate-depleted placebo three hours before exercise, and caffeine (5 mg·kg-1) or maltodextrin placebo one hour before testing. EP and WEP were determined from the 3MT. Secondary outcomes included peak and mean power output. Data were analyzed using a repeated-measures ANOVA with repeated measures on condition. A p-value of 0.05 was used to determine statistical significance. Effect size was evaluated using partial eta squared. Results: No significant effect of condition was observed for EP (p = 0.401, Etap2 = 0.056), WEP (p = 0.580, Etap2 = 0.048), peak power (p = 0.642, Etap2 = 0.046), mean power (p = 0.212, Etap2 = 0.108), or total work (p = 0.217, Etap2 = 0.107). Conclusions: No statistically significant differences between conditions were detected under the conditions of the present study.